FETAL MUMMIFICATION DUE TO TORSION OF UMBLICAL CORD IN A COW - PANDEY, ANAND KUMAR; SINGH, GYAN; PHOGAT, J B; PANIHAR, S; SHYAMSUNDER (The Indian Journal of Animal Reproduction, 2011)
Successful delivery through caesarian section of mummified fetus due to umbilical torsion in a Haryana cow after failing veterinary medical intervention has been described.